Low temperature combustion synthesis of nitrogen-doped graphene for metal-free catalytic oxidation - Indrawirawan, S.; Sun, Hongqi; Duan, X.; Wang, Shaobin (R S C Publications, 2015)
Nitrogen-doped reduced graphene oxide (N-rGO) was prepared by a simple process of simultaneous reduction and nitrogen doping on graphene oxide (GO) at low temperatures using ammonium nitrate as a N precursor. Characterization techniques indicated that N-rGO materials with a high N loading (5–8 at%) can be easily produced and that the crystal/micro-structures and chemical compositions of N-rGO materials are dependent on the calcination conditions. The metal-free catalysis of N-rGO was investigated by catalytic activation of peroxymonosulfate (PMS) for phenol oxidative degradation in water. It was found that N-rGO samples are promising green catalysts for phenol degradation. Kinetic studies showed that phenol degradation follows first order reaction kinetics on N-rGO-350 with an activation energy of 31.6 kJ mol−1. The mechanism of PMS activation and phenol oxidation was elucidated by employing both electron paramagnetic resonance (EPR) studies and quenching tests with ethanol and tert-butanol.